2021
DOI: 10.1002/csc2.20599
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen source effects on canola (Brassica napus L.) grown under conservation agriculture in South Africa

Abstract: Canola (Brassicanapus L.) growth and yield can be enhanced by, amongst others, choosing the correct rate, source, and timing of N fertilizer. Limited research exists on the effects of nitrogen (N) source on canola growth and yield properties when grown under conservation agriculture. This study compared the performance of different N fertilizer sources on canola biomass production, seed yield, and oil content. Field trials were conducted from 2016 to 2019 at five sites in the Western Cape Province of South Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, Ibrahim et al (1989) reported that the seed oil content and percentage of major fatty acid components were not significantly affected by the nitrogen rates or times [18]. Crous et al (2021) revealed that the nitrogen fertilizer source did not affect the seed oil content, which was determined by the presence of precipitation during the flowering and seed filling stages [19]. The above results suggest that the reduction in rapeseed seed oil content caused by nitrogen application was generally consistent across the different investigations.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, Ibrahim et al (1989) reported that the seed oil content and percentage of major fatty acid components were not significantly affected by the nitrogen rates or times [18]. Crous et al (2021) revealed that the nitrogen fertilizer source did not affect the seed oil content, which was determined by the presence of precipitation during the flowering and seed filling stages [19]. The above results suggest that the reduction in rapeseed seed oil content caused by nitrogen application was generally consistent across the different investigations.…”
Section: Introductionmentioning
confidence: 71%
“…Here, we found that the expression of related genes was mainly high in the early development stages-namely 30-40 days after flowering-and then decreased. According to research, the development stage (30-40 days after flowering) is the rapid accumulation stage of seed oil, which will account for 70.1% to 93.5% of mature seed oil contents, moving into a slow accumulation period up to 50 days [19,41]. In this research, genes were more active at the early sampling time, D1, and then their activity gradually decreased at D2 and D3, which may be the result of the rapid synthesis and transformation of the seed oil.…”
Section: Discussionmentioning
confidence: 99%
“…When possible, changes in soil nutrient dynamics and stratification are considered, and different fertiliser optima than for conventional tillage systems could be expected. For instance, producers in the Western Cape, where CA is well established, are still using nitrogen fertiliser guidelines that were developed under conventional tillage systems (Viljoen et al 2020;Crous et al 2021). These guidelines do not account for the potential supply of mineralised nitrogen from soil organic matter.…”
Section: Soil Fertility Management In Camentioning
confidence: 99%
“…The stratification of nutrients, particularly soil organic matter, underscores the importance of interpreting data with caution, as samples taken at a shallow depth may falsely overestimate the benefits of soil nutrients and soil organic matter. There are confounding recommendations on how to take a soil sample for CA systems (Derpsch et al 2014;Olson and Al-Kaisi 2015). For instance, in soils with a highly stratified pH, a soil acidity problem is often not picked up in soil tests if soil samples are taken to 200 mm or deeper, diluting the stratification effect.…”
Section: Soil Fertility Management In Camentioning
confidence: 99%